A Parent-Facing Decision Aid About Childhood Vaccination: Co-development Study Adapting a Shared Decision-Making Approach to Support Evidence-Guided Decision-Making - Daphne Bussink-Voorend; Lisa Vandeberg; Jeannine LA Hautvast; Glyn Elwyn; Marlies EJL Hulscher (Journal of Participatory Medicine, 2026)
Background Childhood vaccination rates are declining, and more parents are becoming hesitant about vaccinating their children. Higher levels of vaccine hesitancy occur among parents with lower levels of educational attainment, who are also likely to have lower levels of health literacy. Objective We aimed to develop a web-based decision aid, considered a shared decision-making (SDM) approach, to inform and support Dutch parents in their decision-making about routine childhood vaccination, prioritizing the needs of hesitant parents and those with lower health literacy. We adapted the traditional SDM approach by balancing the ethical tension between the collective responsibility for public health and individual autonomy in vaccination decisions and focused the decision aid on evidence-guided (rather than preference-sensitive) decision-making. Methods The development process involved content development and web application development. We adopted a user-centered approach by actively engaging stakeholders, including parents, health professionals, and other experts. Participating stakeholders were purposefully selected and engaged through different routes to include a variety of perspectives. The general concept of vaccination as an evidence-based intervention to promote health at the individual and societal levels remained central throughout the development process. Results We conducted this project in the Netherlands from early 2023 through the end of 2024. We identified parental needs through interviews with 18 parents and a literature assessment. Parental needs, evidence-based information about vaccination, and how to communicate about vaccination informed the initial content of the decision aid. After feedback from the advisory group and subject matter experts, we refined the draft. At this stage, the textual content was inserted into a prototype web application. We subjected this prototype to 3 iterative cycles of testing, review, and adaptation. We analyzed and discussed the issues identified during testing and recommended adaptations to improve the design, structure, and content of the decision aid. These adaptations were subsequently discussed with the advisory group before being implemented. In response to the issues raised, we shortened the text blocks, replaced written information with visual elements, and restructured the layout to improve navigation. The final prototype consisted of the modules “Information” and “Decision Support.” Conclusions We co-developed a parent-facing decision aid (PDA) for childhood vaccination tailored to the needs of hesitant parents and those with lower health literacy. Through this intervention, we adapted an SDM approach to evidence-guided decision-making, creating space for individual concerns and deliberations without compromising evidence-based recommendations. Future research should focus on the timing of the intervention and the optimal window for offering the PDA in relation to the parents’ decision-making process.